Óleo essencial de Cymbopogon citratus : atividade antifúngica em Alternaria solani e ativação de mecanismos de defesa em tomateiro - Itako, Adriana Terumi (2008)
This study had the objective of evaluating the effect of essential oil of Cymbopogon citratus in vitro and in vivo in development of Alternaria solani and in induced biochemical and structural resistance mechanisms. In vitro were evaluatied the micelial growth and sporulation. Tomato plants were preventively treated (72 hours before inoculation) with essential oil in 0, 250, 500, 750, 1000 and 1500 μL L-1 concentrations. To determinate peroxidase, polyphenoloxidase and β-1,3 glucanase activity, leaves discs were collected 0, 12, 24 and 48 h after inoculation. The 48 h time was also used to evaluate germination, apressory formation and structural resistance mechanisms formation. In vitro results showed direct toxic activities, however, in in vivo conditions, the essential oil had no fungitoxic effect on spores in tested conditions. The peroxidase and polyphenoloxidase activity showed enhance local and systemicly. The β-1,3 glucanase activity showed enhance only in local leaves in higher concentrations in 48 h. The epidermal analysis demonstrated papillas occurrence and cell lignification in 1000 μL L-1 concentration. These resultsconclude that essential oils of C. citratus have potential of resistance induction in tomato plants.